O imperativo da beleza no Brasil - Denise Bernuzzi de Sant’Anna (Confins)
This text seeks to understand the requirement of beauty among Brazilian and especially the historical construction of the image of the Brazilian seen as always beautiful. This requirement has a history and its critics. It reveals the ancient myths related to the dream of a strong nature and a life full of wealth and happiness. But it also reveals the current imperatives of the aesthetic medicine market and especially to the trivialization of cosmetic surgeries.